Difference in life skills of young volleyball athletes (gender orientation) and identification of supporting factors for their improvement: A mixed method study - Muhamad Ilham; Amung Ma’mun; Yunyun Yudiana; Mustika Fitri; Jusuf Blegur (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Differences in sports disciplines impact athletes' life skills (LS), and this is greatly influenced by the model and strategy of integrating LS into the training program. Objective: This study aims to examine the differences in LS between male and female athletes and to identify the factors contributing to the improvement of LS. Methodology: The researcher used a mixed method with an explanatory sequential design. The quantitative study sample totaled 51 young athletes (23 males and 28 females). Quantitative data was collected using the 47-item Life Skills for Sport Scale and analyzed descriptively and statistically independent samples t-test. There were six qualitative respondents. Qualitative data were collected using 47 semi-structured interview guidelines and analyzed thematically. Results: There were no significant differences between the two sample groups, but female athletes had a better LS. Six of the eight LS indicators showed significant differences: time management, emotional skills, interpersonal communication, social skills, leadership, and problem-solving and decision-making. Discussion: Experiences that contribute to improving young athletes’ LS are providing opportunities to discuss and evaluate training results, playing the role of team captain or group leader, setting a clear training schedule for each training component, being open to mistakes in order to control emotions better, training in pairs or groups to encourage closer relationships, and simulating various problems or challenges during training. Conclusions: Future researchers need to design a LS integration program to address the LS issues of young athletes.